2023
DOI: 10.3389/fneur.2023.1187666
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of community-based exercise programs on circulating irisin level, muscle strength, cardiorespiratory endurance, and body composition for ischemic stroke: a randomized controlled trial

Abstract: ObjectiveWe investigated the changes in circulating irisin levels after community-based exercise and the association of these levels with improvements in muscle strength, cardiorespiratory endurance, and body composition in people with ischemic stroke.MethodsTwenty participants were randomly assigned to either a control or an exercise group. The community-based exercise program (CEP) consisted of 8 weeks of 1 h sessions for 3 days a week. Irisin levels, muscle strength, cardiorespiratory endurance, and body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…(16) In instances of ischemic stroke, physical activity has the potential to enhance the circulation of irisin. (17) In the aftermath of cerebral ischemia, physical exercise, particularly using activating irisin, could potentially decrease mortality rates and enhance cognitive function. (18) A study has demonstrated that irisin can impede the damage inflicted upon neurons by ischemia.…”
mentioning
confidence: 99%
“…(16) In instances of ischemic stroke, physical activity has the potential to enhance the circulation of irisin. (17) In the aftermath of cerebral ischemia, physical exercise, particularly using activating irisin, could potentially decrease mortality rates and enhance cognitive function. (18) A study has demonstrated that irisin can impede the damage inflicted upon neurons by ischemia.…”
mentioning
confidence: 99%